2023
DOI: 10.3390/plants12081605
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Biochar and Silicon in Improving Physio-Biochemical and Yield Characteristics of Borage Plants under Different Irrigation Regimes

Abstract: Silicon (Si) and biochar (Bc) are key signaling conditioners that improve plant metabolic processes and promote drought tolerance. However, the specific role of their integrative application under water restrictions on economical plants is not yet well understood. Two field experiments throughout 2018/2019 and 2019/2020 were conducted to examine the physio-biochemical modifications and yield attributes of borage plants mediated by Bc (9.52 tons ha−1) and/or Si (300 mg L−1) under different irrigation regimes (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 110 publications
0
5
0
Order By: Relevance
“…Conversely, earlier investigations displayed a reduction in chlorophyll levels resulting from the decline in the assimilation of 5-aminolinolic acid, an essential intermediate of protochlorophyllide, which transforms into chlorophyll in light conditions [65]. Furthermore, salt stress persuades a decline in chlorophyll assimilation of intermediation and reductions in the expression of ChlD, Chl H, and Chl I-1 gene encoding subunits of Mg-chelatase [66,67]. Current results revealed that the spraying of SA boosted chlorophyll accumulation in salt-affected plants.…”
Section: Discussionmentioning
confidence: 96%
“…Conversely, earlier investigations displayed a reduction in chlorophyll levels resulting from the decline in the assimilation of 5-aminolinolic acid, an essential intermediate of protochlorophyllide, which transforms into chlorophyll in light conditions [65]. Furthermore, salt stress persuades a decline in chlorophyll assimilation of intermediation and reductions in the expression of ChlD, Chl H, and Chl I-1 gene encoding subunits of Mg-chelatase [66,67]. Current results revealed that the spraying of SA boosted chlorophyll accumulation in salt-affected plants.…”
Section: Discussionmentioning
confidence: 96%
“…Crops possess a unique defense mechanism to eradicate ROS and preserve redox homeostasis in stressful situations [11]. The antioxidant system includes enzymatic and non-enzymatic antioxidants [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, ND accelerates the over-production of reactive oxygen species (ROS) that causes ubiquitous cellular destruction and dysfunction of numerous physio-molecular responses [7,8]. Within oxidative stress, crops possess a distinct protection approach for eradicating ROS and maintaining redox homeostasis [9][10][11]. As a result, boosting ND tolerance is an effective strategy for lowering nitrogen leakage and environmental pollution caused by excessive N fertilization.…”
Section: Introductionmentioning
confidence: 99%
“…The degeneration in chlorophyll, once salinity occurs, could result from the drop in chlorophyll biosynthetic or boosted enzymatic chlorophyll deprivation [61], in addition, the degeneration of the thylakoid membranes and devastation of chlorophyll by diverse ROS, and alterations in chlorophyll protein complexes [62]. Moreover, salinity may induce a deterioration in chlorophyll biosynthesis intermediation and decrease the expression of ChlD, Chl Hand Chl I-1 gene encoding subunits of Mg-chelatase [63,64]. As indicated in the current findings and earlier research, utilization of HA has been recorded to improve chlorophyll accumulation in plants within stress or non-stress circumstances [65,66].…”
Section: Discussionmentioning
confidence: 99%